Synthesis and Antipestal Studies of a Novel Heterocyclic Multidentate Schiff Base and its Transition Metal Complexes - Kumar, Hemant; Pal Chaudhary, Ram (Asian Journal of Chemistry, 2011)
A new heterocyclic multidentate Schiff base ligand bis[2-(6-methylpyridin-2-ylimino)phenyl]- 4,4'-(diazene-1,2-diyl)dibenzoate (BMDD, L) and its metal chelates with some transition metal ions viz., Co(II), Ni(II), Cu(II) and Zn(II) have been synthesized and characterized through various spectral data and elemental analyses. The ligand BMDD acts as a hexadentate ligand and forms six-coordinated complexes with all these metal ions through two imine nitrogens, two carbonyl oxygens and two pyridine nitrogens. The ligand and its metal complexes have been screened for the antipestal activities towards Tribolium castaneum a red flour bettle as a storage food grain pest commonly found in India. The results showed that all the metal complexes have higher antipestal activities than the ligand. The order of antimicrobial activities was in order: Cu(II)L > Zn(II)L > Ni(II)L > Co(II)L > L.